Clinical Effects of a Home Care Pilot Program for Patients with Type 1 Diabetes Mellitus: A Retrospective Cohort Study - Lee, Sejeong; Kim, KyungYi; Kim, Ji Eun; Hyun, Yura; Lee, Minyoung; Hahm, Myung-Il; Lee, Sang Gyu; Kang, Eun Seok (Diabetes & metabolism journal, 2023)
Background: Given the importance of continuous self-care for people with type 1 diabetes mellitus (T1DM), the Ministry of Health and Welfare of Korea launched a pilot program for chronic disease management. Herein, we applied a home care pilot program to people with T1DM to investigate its effects.Methods: This retrospective cohort study was conducted at a single tertiary hospital (January 2019 to October 2021). A multidisciplinary team comprising doctors, nurses, and clinical nutritionists provided specialized education and periodically assessed patients’ health status through phone calls or text messages. A linear mixed model adjusting for age, sex, and body mass index was used to analyze the glycemic control changes before and after implementing the program between the intervention and control groups.Results: Among 408 people with T1DM, 196 were enrolled in the intervention group and 212 in the control group. The reduction in glycosylated hemoglobin (HbA1c) after the program was significantly greater in the intervention group than in the control group (estimated marginal mean, –0.57% vs. –0.23%, P=0.008); the same trend was confirmed for glycoalbumin (GA) (–3.2% vs. –0.39%, P<0.001). More patients achieved the target values of HbA1c (<7.0%) and GA (<20%) in the intervention group than in the control group at the 9-month follow-up (34.5% vs. 19.6% and 46.7% vs. 28.0%, respectively).Conclusion: The home care program for T1DM was clinically effective in improving glycemic control and may provide an efficient care option for people with T1DM, and positive outcomes are expected to expand the program to include more patients.